Industrial batch production method of calcium-based adsorbent particles with high CO2 adsorbability
By combining the ball mill modification method and the extrusion molding method, the problem of the compact internal structure of calcium-based adsorbent particles is solved, and the industrial batch preparation of high-performance calcium-based adsorbent particles is realized, which improves the CO2 capture performance and has industrial application prospects.
Patent Information
- Application Number
- CN202411870977.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
AI Technical Summary
During the extrusion molding process, the internal structure of the existing calcium-based adsorbent granules is too dense, resulting in low CO2 capture performance. At the same time, the existing modification methods are difficult to achieve industrialized large-scale preparation.
The ball mill modification method is combined with the extrusion molding method, and the specific surface area and pore volume of the powder are increased by adding support material to the calcium-based powder, thereby improving the CO2 capture performance of the calcium-based adsorbent particles.
The CO2 capture performance of calcium-based adsorbent particles has been improved. The cumulative CO2 adsorption capacity of ten cycles can be increased by 5.6-17.3% compared with ordinary calcium-based adsorbent particles. The process flow is simple and the production efficiency is high, and it has the prospect of industrial application.
Smart Images

Figure CN119633741A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon dioxide capture, and more specifically, to a method for industrial mass production of calcium-based adsorbent particles with high CO2 adsorption. Background Art
[0002] Human-made CO2 emissions are mainly concentrated in large-scale fossil energy utilization industries such as thermal power generation, steel production, cement production, and transportation. CO2 capture, utilization and storage (CCUS) is the main strategy that can better achieve large-scale CO2 emission reduction.
[0003] The calcium looping (CaL) technology based on the carbonation / calcination cycle of calcium-based adsorbents to adsorb CO2 can be used for post-combustion CO2 capture technology in CCUS. It mainly uses calcium-based adsorbents (i.e. calcium oxide) to capture CO2 from the tail gas of existing power station boilers, cement kilns, industrial kilns and other combustion equipment to reduce the system's CO2 emissions. Calcium-based adsorbents need to be prepared into particles during the application of calcium loop technology. Currently, calcium-based adsorbent granulation methods include extrusion molding, spheroidization, cladding, extrusion spheronization and casting. Among them, the extrusion method has the highest adsorbent particle preparation efficiency and is suitable for industrial production applications. However, the particles prepared by the extrusion method have relatively low carbon capture performance due to their overly dense internal structure. Some researchers have improved the carbon capture performance of adsorbent particles through acid modification, high-temperature pre-sintering, steam activation, inert skeleton doping, alkali metal salt modification, sol-gel method, flame synthesis method, etc. However, these modification methods are still in the laboratory research and development stage and cannot be applied industrially. It is difficult to achieve large-scale preparation of high-performance calcium-based adsorbent particles.
[0004] Therefore, in response to the above problems, a method suitable for the industrial mass production of high-performance calcium-based CO2 adsorbent particles has been developed, in order to achieve large-scale production of high-performance calcium-based CO2 adsorbent particles to meet the carbon capture needs of industries such as thermal power generation, steel production, cement production, and transportation. Summary of the invention
[0005] There are two main technical problems to be solved by the present invention. The first is to improve the carbon capture performance of calcium-based adsorbent particles. The extrusion molding method for preparing calcium-based adsorbent particles has the greatest potential for industrial application due to its high production efficiency. However, since the internal structure of the particles prepared by the extrusion molding method is too dense, it is difficult for CO2 to diffuse into the interior of the particles, resulting in low carbon capture performance of the adsorbent particles; the second is to achieve industrial mass production of high-performance calcium-based adsorbent particles. Existing acid modification, high-temperature pre-sintering, steam activation, inert skeleton doping, alkali metal salt modification, sol-gel method, flame synthesis method and other means can improve the carbon capture performance of adsorbent particles, but these means are complex and costly, and it is difficult to achieve industrial application at the current stage. In response to the above two problems, the present invention proposes a method for industrial mass production of calcium-based adsorbent particles with high CO2 adsorption. The method is based on the extrusion molding method and combined with the ball milling modification method to improve the carbon capture performance of calcium-based adsorbent particles. At the same time, the method has a simple process flow, high production efficiency, and has prospects for industrial application.
[0006] According to a first aspect of the present invention, there is provided a method for industrial batch production of calcium-based adsorbent particles, comprising the following steps:
[0007] (1) adding a support material with aluminum oxide as a main component to a calcium-based powder, and then ball milling to obtain a fully mixed powder; the calcium-based powder is slaked lime or limestone;
[0008] (2) adding water to the powder obtained in step (1) to mix the powder to obtain a homogeneous mass-like mud material;
[0009] (3) adding the agglomerated mud obtained in step (2) into an extruder to extrude into strips, cutting into particles, and then drying;
[0010] (4) calcining the dried particles obtained in step (3) to obtain calcium-based adsorbent particles.
[0011] Preferably, the mass ratio of the calcium-based powder to the support material is 9:(1-3).
[0012] Preferably, the support material is cordierite, pseudo-boehmite, bauxite, kaolin or bentonite.
[0013] Preferably, the rotation speed of the ball mill is 300-500 r / min, the ball-to-material ratio is 5:(1-25), and the ball milling time is 0.5h-2h.
[0014] Preferably, the calcination temperature is 700-900°C.
[0015] Preferably, the drying temperature is 80-110°C.
[0016] Preferably, in step (3), the diameter of the particles is 5-6 mm.
[0017] Preferably, in step (3), the length of the particles is 5-6 mm.
[0018] Preferably, the ball mill used in the ball milling is a planetary ball mill.
[0019] According to another aspect of the present invention, provided are prepared calcium-based adsorbent particles.
[0020] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0021] (1) The ball milling modification method of the present invention can produce multiple effects on the material: first, it makes the powder mixing more uniform; second, it breaks the large-size powder in the powder into a smaller size, thereby increasing the specific surface area and pore volume of the powder; third, when the powder is continuously crushed between the grinding balls, it will accumulate excessive potential energy, resulting in the breaking of internal chemical bonds, forming defects and making the material tend to an amorphous structure; these three effects can all improve the carbon capture performance of the adsorbent.
[0022] (2) The extrusion molding method mainly includes three steps: powder mixing, material agglomeration, and extrusion molding. Ball milling modification is essentially a modification by mechanical grinding in a ball mill, which can also play the role of powder mixing, and the powder mixing is more uniform. Using ball milling modification to replace the powder mixing step in the extrusion molding method can not only improve the uniformity of powder mixing, but also will not make the process cumbersome, with high production efficiency and great prospects for industrial application.
[0023] (3) The method proposed in the present invention combines the ball milling modified extrusion molding method. Compared with the ordinary extrusion molding method, the calcium-based adsorbent particles produced by the method have better carbon capture performance and cycle stability. The cumulative CO2 adsorption capacity of the high-performance calcium-based adsorbent particles after ten cycles can be increased by 5.6-17.3% compared with ordinary calcium-based adsorbent particles.
[0024] (4) The present invention combines the extrusion molding method with ball milling modification, and still retains the simple steps of the extrusion molding method. It only replaces the original powder mixing process with the ball milling modification process, and does not overly complicate the process flow. Compared with the spheroidization method, the cladding method, the extrusion spheronization method and the casting method, the present invention has the highest production efficiency and the most promising industrial application prospects.
[0025] (5) Compared with acid modification, high-temperature pre-sintering, steam activation, inert skeleton doping, alkali metal salt modification, sol-gel method, flame synthesis method and other modification methods, the ball milling modification process of the present invention is simple to operate, has high output, and is time-saving, and can be perfectly coupled with the extrusion molding method; moreover, the ball mill used in the ball milling modification method has long been industrialized in the mining, metallurgy and other industries, and has a strong basis for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the process flow of the present invention.
[0027] Figure 2 The CO2 capture performance of the calcium-based adsorbent particles of Examples 1-3 and Comparative Example 1.
[0028] Figure 3 The CO2 capture performance results of the calcium-based adsorbent particles of Examples 1-3 and Comparative Example 1 for ten cycles.
[0029] Figure 4 The SEM characterizations of Example 3 and Control Example 1, wherein (a) is the SEM characterization of the sample particles of Example 3, and (b) is the SEM characterization of the sample particles of Control Example 1.
[0030] Figure 5 These are the EDS element distribution diagrams of Example 3 and Control Example 1, wherein (a) is the Ca, Si, and Al element distribution diagram of the calcium-based adsorbent particles of Example 3, and (b) is the Ca, Si, and Al element distribution diagram of the calcium-based adsorbent particles of Control Example 1. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0032] The present invention proposes a method for industrial mass production of calcium-based adsorbent particles with high CO2 adsorption. The detailed process flow of the method is as follows:
[0033] (1) Weigh a certain amount of calcium hydroxide powder (not limited to calcium hydroxide, but also other calcium-based powders such as limestone, preferably calcium hydroxide), add a certain amount of cordierite (whose main components are aluminum oxide and silicon oxide. In addition to cordierite, various supports such as pseudo-boehmite, bauxite, kaolin, bentonite, high-alumina cement, etc. can also be added. Cordierite is preferred).
[0034] (2) The weighed calcium hydroxide and cordierite powders are placed in a grinding jar, a certain amount of ball milling beads are added thereto, and then the grinding jar is fixed in a planetary ball mill, and ball milling is performed at a speed of 300-500 r / min. After the ball milling is completed, the ball milling beads and the powder mixture are screened using a sieving machine to obtain a uniformly mixed mixture of calcium hydroxide and cordierite powders. (The present invention does not specifically limit the amount of ball milling beads added, the ball milling time, and the ball milling speed in the ball milling modification method, as long as the powder can be fully mixed and ball milled. The present invention preferably has a mass ratio of ball milling beads to powder in the range of 1:5 to 5:1; the preferred ball milling time is 0.5-2h; and the preferred ball milling speed is 300r / min.)
[0035] (3) Put the appropriate proportion of water and powder mixture into a fully automatic mixer to mix and form a homogeneous mass of mud.
[0036] (4) The lump-like mud material is extruded into strips by a hydraulic extruder and cut by an automatic cutting machine. The cut particles are placed in a drying oven and dried at 80-110° C. to obtain particles with a diameter of 5-6 mm and a length of 5-6 mm.
[0037] (5) placing the particles in a high-temperature atmosphere furnace for high-temperature calcination, wherein the temperature of the atmosphere furnace ranges from 700 to 900° C., and dry air is continuously introduced into the furnace during the calcination process. After the calcination is completed, calcium-based adsorbent particles can be obtained.
[0038] The process flow diagram of the present invention is as follows Figure 1 shown.
[0039] The present invention couples the ball milling modification method with the extrusion molding method to achieve industrial batch preparation of high-performance calcium-based adsorbent particles. First, the ball milling modification method makes the powder mixing more uniform by continuous grinding; second, the particle size of the powder becomes smaller during the continuous grinding process, and its specific surface area and pore volume are improved, so that the microscopic pore structure of the adsorbent particles is richer, which is conducive to the diffusion and adsorption of carbon dioxide, and significantly improves the CO2 capture performance of the adsorbent particles; third, the ball milling modification method can replace the powder mixing step in the extrusion molding method, and does not add unnecessary steps. In the actual production process of adsorbent particles, the process flow is not complicated; fourth, the ball milling modification method can be realized only by a ball mill, and the ball mill has long been applied in the factory. Therefore, the high-performance calcium-based adsorbent particle preparation method coupled with the ball milling modification method and the extrusion molding method has strong industrial application potential and prospects.
[0040] The ball milling modification method is generally implemented by a ball mill, but in the actual industrial production process of high-performance calcium-based adsorbent particles, when grinding and mixing powders, rod mills, autogenous mills, stirred mills and other means can also be used to grind and mix powders, which can obtain adsorbent powders with relatively uniform mixing and good carbon capture performance, but its specific grinding time and other parameters need to be determined according to the equipment model and performance. However, the ball mill, especially the planetary ball mill used in the present invention, revolves around the center of the grinding disk while rotating, and the direction of rotation is usually opposite to the direction of revolution to avoid centrifugal phenomena. This feature makes the planetary ball mill mainly rely on the huge inertial force of the grinding medium rather than gravity to achieve the crushing and grinding of the material. Compared with other grinding methods, its grinding effect is better and the efficiency is higher.
[0041] In the following specific examples, slaked lime is a commercial product, the main component of which is Ca(OH)2, with a mass percentage of 90-95%; cordierite is a commercial product, the main components of which are alumina and silicon oxide. The CO2 capture performance of sample powder and sample particles was tested using a synchronous thermal analyzer (STA) and a fixed bed reactor respectively; SEM, BET, and EDS were used to perform microscopic analysis and comparison of the samples.
[0042] Synchronous thermal analyzer sample cycle CO2 capture performance test: Synchronous thermal analyzer STA 2500Regulus produced by NETZSCH, Germany was used. For each test, about 10 mg of the test sample was loaded into a 40 μl alumina crucible, and the test was carried out according to the following procedure: First, the sample was pre-calcined in a 100 ml / min N2 atmosphere: the temperature was increased from 20°C to 850°C at a heating rate of 30°C / min, and the constant temperature was maintained for 20 minutes to ensure that the residual Ca(OH)2 and CaCO3 in the sample were completely decomposed. Then the temperature was reduced from 850°C to 650°C at a cooling rate of 30°C / min. At a temperature of 650°C, the atmosphere was adjusted to 15 ml / min CO2+85 ml / min N2 for carbonation test, and the time was 60 minutes. After the carbonation stage, the atmosphere was adjusted to 100 ml / min of N2 atmosphere, and the temperature was raised from 650°C to 850°C at a rate of 30°C / min to enter the calcination stage. The constant temperature time was 10 minutes to complete the decomposition of CaCO3 in the calcium-based carbon dioxide adsorbent and the regeneration of CaO. Each cycle includes a carbonation stage and a calcination stage. Each sample was subjected to a multi-cycle adsorption performance test, and the CO2 adsorption capacity of the sample in each cycle was calculated.
[0043] Fixed bed reactor sample CO2 capture performance test: 10g of calcium-based adsorbent sample was loaded into a vertical fixed bed reactor, and simulated flue gas was introduced for performance evaluation. The test operating conditions of the fixed bed reactor were: simulated flue gas flow rate of 1L / min, composition of 15% CO2 and 85% N2, adsorption temperature of 650℃, and reaction time of 120min. The CO2 adsorption capacity of the calcium-based adsorbent sample was measured.
[0044] The CO2 capture performance of the calcium-based adsorbent sample is defined by the CO2 adsorption capacity of the calcium-based adsorbent sample, and the specific formula is as follows:
[0045]
[0046] In the formula: N is the number of cycles; C N is the CO2 adsorption capacity of the Nth cycle calcium-based adsorbent sample, in gCO2 / g adsorbent; m car,N is the mass of the calcium-based adsorbent sample after the Nth cycle of carbonation; m cal,N is the mass of the calcium-based adsorbent sample after the Nth cycle of calcination.
[0047] The following are specific examples and comparative examples.
[0048] Example 1
[0049] The preparation process of the present invention is as follows Figure 1 As shown, 422.8 g of slaked lime powder and 80 g of cordierite are put into a zirconia grinding jar, and zirconia ball milling beads are added to ensure that the mass ratio of the ball milling beads to the powder sample is 1:5. The ball milling jar is then sealed and fixed on a planetary ball mill. The ball milling is carried out at a speed of 300 r / min for 1 h. After the ball milling is completed, the ball milling beads and the powder mixture are sieved using a sieving machine to obtain a uniformly mixed mixture of calcium hydroxide and cordierite powder.
[0050] Then put the powder mixture into a fully automatic mixer, add water in appropriate proportions, and repeatedly mix the materials into a mass, eventually forming a fine and homogeneous mass of mud.
[0051] The lump mud is taken out and then put into a fully automatic hydraulic extruder, the lump mud is extruded into strips, and cut with an automatic cutting machine, the cut particles are put into a drying oven, and dried at 80-110°C to obtain particles with a diameter of 5-6mm and a length of 5-6mm.
[0052] The particles are transferred to a high-temperature atmosphere furnace and calcined at high temperature under high-flow dry air purge conditions, wherein the atmosphere furnace temperature range is 850°C, the air flow rate is 10L / min, and the calcination time is 120min. After calcination, high-performance calcium-based adsorbent particles can be obtained.
[0053] The high-performance calcium-based adsorbent particle sample prepared by the method described in Example 1 was subjected to a CO2 capture performance test in a fixed bed reactor. The experimental test conditions and operating conditions were as above. The CO2 adsorption capacity of the sample in Example 1 was measured to be 0.511 gCO2 / g adsorbent.
[0054] Example 2
[0055] The preparation process of the present invention is as follows Figure 1 As shown, 422.8 g of slaked lime powder and 80 g of cordierite are put into a zirconia grinding jar, and zirconia ball milling beads are added to ensure that the mass ratio of the ball milling beads to the powder sample is 1:1. The ball milling jar is then sealed and fixed on a planetary ball mill. The ball milling is carried out at a speed of 300 r / min for 1 h. After the ball milling is completed, the ball milling beads and the powder mixture are sieved using a sieving machine to obtain a uniformly mixed mixture of calcium hydroxide and cordierite powder.
[0056] Then put the powder mixture into a fully automatic mixer, add water in appropriate proportions, and repeatedly mix the materials into a mass, eventually forming a fine and homogeneous mass of mud.
[0057] The lump mud is taken out and then put into a fully automatic hydraulic extruder, the lump mud is extruded into strips, and cut with an automatic cutting machine, the cut particles are put into a drying oven, and dried at 80-110°C to obtain particles with a diameter of 5-6mm and a length of 5-6mm.
[0058] The particles are transferred to a high-temperature atmosphere furnace and calcined at high temperature under high-flow dry air purge conditions, wherein the atmosphere furnace temperature range is 850°C, the air flow rate is 10L / min, and the calcination time is 120min. After calcination, high-performance calcium-based adsorbent particles can be obtained.
[0059] The high-performance calcium-based adsorbent particle sample prepared by the method described in Example 2 was subjected to a CO2 capture performance test in a fixed bed reactor. The experimental test conditions and operating conditions were as above. The CO2 adsorption capacity of the Example 2 sample was measured to be 0.543 gCO2 / g adsorbent.
[0060] Example 3
[0061] The preparation process of the present invention is as follows Figure 1 As shown, 422.8 g of slaked lime powder and 80 g of cordierite are put into a zirconia grinding jar, and zirconia ball milling beads are added to ensure that the mass ratio of ball milling beads to powder sample is 5:1. The ball milling jar is then sealed and fixed on a planetary ball mill. The ball milling is carried out at a speed of 300 r / min for 1 h. After the ball milling is completed, the ball milling beads and the powder mixture are sieved using a sieving machine to obtain a uniformly mixed mixture of calcium hydroxide and cordierite powder.
[0062] Then put the powder mixture into a fully automatic mixer, add water in appropriate proportions, and repeatedly mix the materials into a mass, eventually forming a fine and homogeneous mass of mud.
[0063] The lump mud is taken out and then put into a fully automatic hydraulic extruder, the lump mud is extruded into strips, and cut with an automatic cutting machine, the cut particles are put into a drying oven, and dried at 80-110°C to obtain particles with a diameter of 5-6mm and a length of 5-6mm.
[0064] The particles are transferred to a high-temperature atmosphere furnace and calcined at high temperature under high-flow dry air purge conditions, wherein the atmosphere furnace temperature range is 850°C, the air flow rate is 10L / min, and the calcination time is 120min. After calcination, high-performance calcium-based adsorbent particles can be obtained.
[0065] The high-performance calcium-based adsorbent particle sample prepared by the method described in Example 3 was subjected to a CO2 capture performance test in a fixed bed reactor. The experimental test conditions and operating conditions were as above. The CO2 adsorption capacity of the sample in Example 3 was measured to be 0.563 gCO2 / g adsorbent.
[0066] Comparative Example 1
[0067] 422.8 g of slaked lime powder and 80 g of cordierite were mixed in a V-type dry powder mixer for 1 h to obtain a uniform mixture of calcium hydroxide and cordierite powder.
[0068] Then put the powder mixture into a fully automatic mixer, add water in appropriate proportions, and repeatedly mix the materials into a mass, eventually forming a fine and homogeneous mass of mud.
[0069] The lump mud is taken out and then put into a fully automatic hydraulic extruder, the lump mud is extruded into strips, and cut with an automatic cutting machine, the cut particles are put into a drying oven, and dried at 80-110°C to obtain particles with a diameter of 5-6mm and a length of 5-6mm.
[0070] The particles are transferred to a high-temperature atmosphere furnace and calcined at high temperature under a large flow rate of dry air purge conditions, wherein the atmosphere furnace temperature range is 850°C, the air flow rate is 10L / min, and the calcination time is 120min. After the calcination is completed, the calcium-based adsorbent particles can be obtained.
[0071] The calcium-based adsorbent particle sample prepared by the method described in this Control Example 1 was subjected to a CO2 capture performance test in a fixed bed reactor. The experimental test conditions and operating conditions were as above. The CO2 adsorption capacity of the Control Example 1 sample was measured to be 0.489 gCO2 / g adsorbent.
[0072] Figure 2The CO2 capture performance test results of the calcium-based adsorbent particles prepared in Examples 1-3 and Comparative Example 1 were conducted on a fixed bed reactor. Comparative Example 1 is a calcium-based adsorbent particle prepared by ordinary mixing, and its CO2 capture performance is only 0.489 gCO2 / g adsorbent, while the calcium-based adsorbent particles of Examples 1-3 prepared by ball milling modification have improved CO2 capture performance.
[0073] Figure 3 Table 1 and Table 1 are the results of ten-cycle CO2 capture performance of the calcium-based adsorbent particles prepared in Examples 1-3 and Comparative Example 1 measured on a synchronous thermal analyzer (STA). The ten-cycle CO2 capture performance of the calcium-based adsorbent particles in Comparative Example 1 prepared by mechanical mixing is lower than that of the calcium-based adsorbent particles in Examples 1-3 prepared by ball milling modification. Therefore, the ball milling modification method is coupled with the extrusion molding method to prepare calcium-based adsorbent particles with higher adsorption performance and better adsorbent cycle stability. In addition, the method has simple operating steps, high output, and short time consumption. Using this method, 500g of high-performance calcium-based adsorbent particles can be produced in the laboratory in four hours. Based on an average of eight working hours per day, 1kg of high-performance calcium-based adsorbent particles can be produced on a laboratory scale. Therefore, this method has great prospects for industrial application.
[0074] Table 1 CO2 capture performance results of ten cycles of calcium-based adsorbent particles in Examples 1-3 and Comparative Example 1
[0075]
[0076]
[0077] At the same time, SEM, EDS, and BET were used to characterize and analyze the high-performance calcium-based adsorbent particles of Example 3 and the ordinary calcium-based adsorbent particles of Comparative Example 1 at the microscopic level. Figure 4 , Figure 5 As can be seen from the results in Table 2, the high-performance calcium-based adsorbent particles of Example 3 prepared by the ball milling modification method have a smaller particle size, a larger specific surface area and a larger total pore volume, a more developed pore structure that is more conducive to the diffusion of CO2 molecules inside it, and a more uniform distribution of elements inside the sample. Therefore, the adsorbent particles have better CO2 capture performance and adsorbent cycle stability.
[0078] Table 2 BET test results
[0079]
[0080] The present invention proposes a method for industrial mass production of calcium-based adsorbent particles with high CO2 adsorption, and achieves kilogram-level preparation in the laboratory. The method proposed by the present invention couples ball milling modification with extrusion molding. Compared with existing acid modification, high-temperature pre-sintering, water vapor activation, inert skeleton doping, alkali metal salt modification, sol-gel method, flame synthesis method and other methods, its process flow is simple to operate, with low energy consumption, high efficiency, and large output, and kilogram-level preparation can be achieved in the laboratory; at the same time, the carbon capture performance of the calcium-based adsorbent particles prepared by this method is improved by 5.6-17.3% compared with ordinary adsorbent particles, and the carbon capture performance has good cycle stability, which has great prospects for industrial application and can provide strong support for the carbon capture needs of thermal power generation, steel production, cement production, transportation and other industries.
[0081] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for industrial batch production of calcium-based adsorbent particles, characterized in that: The following steps are involved: (1) adding a support material with aluminum oxide as a main component to a calcium-based powder, and then ball milling to obtain a fully mixed powder; the calcium-based powder is slaked lime or limestone; (2) adding water to the powder obtained in step (1) to mix the powder to obtain a homogeneous mass-like mud material; (3) adding the agglomerated mud obtained in step (2) into an extruder to extrude into strips, cutting into particles, and then drying; (4) calcining the dried particles obtained in step (3) to obtain calcium-based adsorbent particles.
2. The method for industrial mass production of calcium-based adsorbent particles according to claim 1, characterized in that: The mass ratio of the calcium-based powder to the support material is 9:(1-3).
3. The method for industrial mass production of calcium-based adsorbent particles according to claim 1 or 2, characterized in that: The support material is cordierite, pseudo-boehmite, bauxite, kaolin or bentonite.
4. The method for industrial mass production of calcium-based adsorbent particles according to claim 1, characterized in that: The rotation speed of the ball mill is 300-500 r / min, the ball-to-material ratio is 5:(1-25), and the ball milling time is 0.5h-2h.
5. The method for industrial mass production of calcium-based adsorbent particles according to claim 1, characterized in that: The calcination temperature is 700-900°C.
6. The method for industrial mass production of calcium-based adsorbent particles according to claim 1, characterized in that: The drying temperature is 80-110°C.
7. The method for industrial mass production of calcium-based adsorbent particles according to claim 1, characterized in that: In step (3), the diameter of the particles is 5-6 mm.
8. The method for industrial mass production of calcium-based adsorbent particles according to claim 1, characterized in that: In step (3), the length of the particles is 5-6 mm.
9. The method for industrial mass production of calcium-based adsorbent particles according to claim 1, characterized in that: The ball mill used in the ball milling is a planetary ball mill.
10. Calcium-based adsorbent particles prepared according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing calcium-based oxygen carrier
CN104164273A
Method for synthesizing fly ash stabilized calcium-based CO2 adsorbent with mechanical ball milling method
CN106390914A
Calcium-based adsorbent as well as preparation method and application thereof
CN118002067A
Preparation method of MgO-based adsorbent particles
CN118594464A
Method for batch preparation of calcium-based adsorbent particles with high CO2 adsorbability through wet mixing mechanical modification
CN119565557A